Isolation and molecular characterization of the ribosomal protein L6 homolog from Chlamydia trachomatis. - Gray, G J (1991)
The cloning of a Chlamydia trachomatis eukaryotic cell-binding protein reported earlier from our laboratory (R. Kaul, K. L. Roy, and W. M. Wenman, J. Bacteriol. 169:5152-5156, 1987) represents an artifact generated by nonspecific recombination of chromosomal DNA fragments. However, the amino terminus of this plasmid-encoded fusion product demonstrated significant homology to Escherichia coli ribosomal protein L6. By using a 458-bp PstI-HindIII fragment of recombinant pCT161/18 (representing the 5' end of the cloned gene), we isolated and characterized a C. trachomatis homolog of the ribosomal protein L6 gene of E. coli. Sequence analysis of an 1,194-bp EcoRI-SacI fragment that encodes chlamydial L6 (designated CtaL6e) revealed a 552-bp open reading frame comprising 183 amino acids and encodes a protein with a molecular weight of 19,839. Interestingly, complete gene homology between C. trachomatis serovars L2 and J, each of which exists as a single copy per genome, was observed. Expression of a plasmid-encoded gene product is dependent on the lac promoter, since no product was obtained if the open reading frame was oriented in opposition to the lac promoter. Immunoblotting of purified ribosomes revealed functional, as well as antigenic, homology between the E. coli and C. trachomatis ribosomal L6 proteins.